Análise biliométrica da produção científica docente do Programa de Pós-Graduação em Educação Especial da UFSCar: 1998-2003. - Silva, Márcia Regina da (2004)
This study it has as main to carry through a bibliometric analysis of the scientific production of the professors of the PPGEEs/UFSCar. This research, that can be fit in the area of studies on the scientific production, consists in a contribution of the area of Information Science for the area of Special Education, which is not only considers to analyze the scientific production, as also in rescuing the performance of this Program of Master Degree as institution that it is dedicated to education and research in the area of Special Education. The universe of the research was composed by 22 professors whose had been involved in the Program from 1998 until 2003. Available the Lattes Resume in the Lattes Platform of CNPQ, was utilized as source of research for recovery of the scientific production associate to each professor. The information contained in the Bibliographical Production of the Lattes Platform had been raised. To leave of this publication survey, it was opted to analyzing articles published in journals, a time that this type of publication more contains brought up to date information on the different research. The obtained results had been analyzed utilizing tools automatized for treatment and bibliometric analysis and had indicated the following aspects with relation to the scientific article publication of the researchers: The published scientific articles represent 7,6% of the total of scientific production in the studied period; between 1998 and 2003 it had a growth of 9,1% of scientific article publications; publication partnership of the professors of the PPGEEs with the other integrant ones of the Program, with professors of the same Line of Research, with professors of different Lines of Research and with external authors to the PPGEEs exists; the majority of publications is carried through in partnership between 2 or more authors; thematic the most boarded one in published articles was "Social Ability"; in journals the Southeastern region the biggest number of in which articles meets had been published; publication partnership exists with authors of the exterior, what it demonstrates the internationalization of the PPGEEs; the majority of scientific articles had been classified in the area of nowledge "Special Education "and in the sector of activity" Education ". Although we know that the Program of Special Education is fit in the area of Sciences Human beings, more specifically in the area of Education, we must always remember that one is about an area to multidiscipline that possess borders with other areas of the knowledge, what it can be observed with the results gotten in this research. The group of professors studied loads obtains its area of formation or research, from there the explanation for the found oscillations, as much of the individual productivity, as in the journals ones chosen for the publication or thematic studied.